Analysis of the Influence of Quality of Education Services and Facilities and Infrastructure on the Trust of the Community of Boarding Boards Az - Ziyadah with Satisfaction as a Mediation Variable - Nurlaila,; Guswandi,; Subagja, Iwan Kurniawan (Krisnadwipayana International Journal of Management Studies, 2022)
This study aims to: 1) test and analyze the effect of Quality of Education Services and Infrastructure Facilities on Satisfaction, 2) test and analyze the effect of Quality of Educational Services Community Trust, 3) test and analyze the effect of Satisfaction on Public Trust, 4) test and analyze the effect of Quality Education Services on Public Trust through Satisfaction, 5) test and analyze the influence of Infrastructure on Public Trust through Satisfaction at the Az Ziyadah Islamic Boarding School, East Jakarta. The research was conducted at the Az Ziyadah Islamic Boarding School in East Jakarta with a research sample of 175 respondents. Sampling technique used is the Simple Random Sampling. The data analysis method used is path analysis. The results of the study show that: 1) There is an influence of Quality Educational Services and Infrastructure Facilities on Satisfaction. 2) There is an influence of the Quality of Educational Services and Infrastructure Facilities on Public Trust. 3) There is an influence of Satisfaction on Public Trust. 4) There is an influence of the Quality of Educational Services on Public Trust through Satisfaction. 5) There is an influence of Infrastructure to Public Trust through Satisfaction at the Az Ziyadah Islamic Boarding School, East Jakarta.